Mysterious Cause of Respiratory Failure and Multilobar Atelectasis in a 17-Month-Old Male. Issue 7 (9th January 2020) - Davis, Gerrit W; Lockett, Casey J; Charny, Grigory
Abstract: A 17-month-old male presented to a community hospital emergency department in respiratory distress suggestive of reactive airway exacerbation or pneumonia. He rapidly deteriorated into fulminant respiratory failure with multilobar atelectasis. He was managed with continuous albuterol, intravenous antibiotics, corticosteroids, intubation, and vasopressors. He was then transported to a tertiary Children's Hospital. The patient was extubated 20 hours after presentation and again developed respiratory failure while in the pediatric intensive care unit. During preparation for extracorporeal membrane oxygenation, he quickly stabilized following reintubation and bronchodilator therapy. He was extubated approximately 24 hours later, and subsequently discharged after a 9-day hospitalization. Outpatient investigation after discharge revealed dysphagia, milk allergy, and eosinophilic esophagitis. In this case, it is highly probable that aspiration secondary to dysphagia and eosinophilic esophagitis led to respiratory failure. This case demonstrates the possible rapid decompensation from aspiration due to insidious inflammation of the esophagus and dysphagia in an otherwise anatomically normal toddler.